The Functional Architecture of Personalized & Precision Medicine (PPM) Driven by Innovative Strategies to Secure the Clinical Impact and Implementation to Cancer Management: Brief Comments - Andronova, Natalia; Grigorieva, Tatiana; Moiseyakh, Marina; Medvedeva, Veronika; Rose, Noel; Dooley, Steven; Abe, Hiroyuki; Zemskov, Andrey; Grishina, Tatiana; Khlynoskii, Aleksandr; Cheng, Holland; Blokh, Sofia; et al. (British Journal of Healthcare and Medical Research, 2022)
The medicine of the XXI century is Personalized & Precision Medicine (PPM), by protecting and preserving human health throughout the life. Creating and maintaining a high level of public health and thus the wellness is a priority in the health sector. In this regard, an upgraded model of healthcare service, which includes the philosophy, principles and armamentarium of PPM and aimed at identifying the disorder at its early (subclinical) stage, is being created and set up. PPM focuses on predictive and preventive measures that contribute to the development of individualized strategies for managing a healthy lifestyle that stabilize morbidity rates and can help to improve the working capacity of the population. Against the background of the development of PPM, there was an explosion and the evolution of the concept of biomarkers (specific bioindicators), whose combinations have been being studied, and their effectiveness and efficacy as working resources were being evaluated.